Kelsen in the reactor hall? The complex interrelationship of national law, European Union law and international law in the regulation of nuclear safety - Fyhr, Kim (Studia Prawa Publicznego, 2023)
This paper focuses on a highly specialized field of law, namely nuclear law. This is characterized, on the one hand, by strong national competences and the primary position of national law, but also, on the other hand, by the international dimension, which has a major impact on national law. For a European Union Member State, the picture is even more wide-ranging, as European Union law, in this case the Euratom Treaty, adds another important layer to the legal-regulatory framework in the nuclear energy sector. The point of departure for this paper is therefore that of an EU Member State, which in nuclear energy issues functions in a legal field consisting of three interdependent main elements – national law, European Union law and international law. Thus, the article seeks to answer the question of which of these three legal systems is the primary one for an EU Member State in the area of nuclear safety, and also to shed light on their interrelationships. he theoretical framework for this analysis aimed at systematization is Hans Kelsen’s classical theory of legal systems. The argument presented here is that for an EU Member State the primary legal system from a legal-hierarchical point of view is the legal system composed of EU law. This is the case mainly because the EU has competence in the area of nuclear safety, albeit shared with the EU Member States. Although the EU/Euratom has not yet significantly expanded regulation in this field, this will most likely change as EU energy policy and legislation develops further in the future. This evolution will most likely have both legislative and enforcement impacts, despite the fact that the substantive content of legislation on all three levels is quite similar. In spite of this, the three legal systems co-exist in constant interaction and without major collisions. Kelsen’s perspective can prove beneficial for understanding the boundaries of the three interdependent legal systems and the shift of the basic norm towards EU law over the past two decades.